Single-nucleotide polymorphisms of the SLC17A9 and P2RY12 genes are significantly associated with phantom tooth pain - Soeda, Moe; Ohka, Seii; Nishizawa, Daisuke; Hasegawa, Junko; Nakayama, Kyoko; Ebata, Yuko; Fukuda, Ken-ichi; Ikeda, Kazutaka (Molecular pain, 2022)
Phantom tooth pain (PTP) is a rare and specific neuropathic pain that occurs after pulpectomy and tooth extraction, but its cause is not understood. We hypothesized that there is a genetic contribution to PTP. We focused on solute carrier family 17 member 9 (SLC17A9)/vesicular nucleotide transporter (VNUT) and purinergic receptor P2Y12 (P2RY12), both of which have been associated with neuropathic pain and pain transduction signaling in the trigeminal ganglion in rodents. We sought to corroborate these associations in humans. We investigated gene polymorphisms that contribute to PTP. We statistically examined the association between genetic polymorphisms and PTP vulnerability in 150 patients with orofacial pain, including PTP, and 500 healthy subjects. We found that the rs735055 polymorphism of the SLC17A9 gene and rs3732759 polymorphism of the P2RY12 gene were associated with the development of PTP. Carriers of the minor allele of rs735055 and individuals who were homozygous for the major allele of rs3732759 had a higher rate of PTP. Carriers of the minor allele of rs735055 reportedly had high SLC17A9 mRNA expression in the spinal cord, which may increase the storage and release of adenosine triphosphate. Individuals who were homozygous for the major allele of rs3732759 may have higher P2RY12 expression that is more active in microglia. Therefore, these carriers may be more susceptible to PTP. These results suggest that specific genetic polymorphisms of the SLC17A9 and P2RY12 genes are involved in PTP. This is the first report on genes that are associated with PTP in humans.